Evaluation of Bulusan Landfill Capacity in Banyuwangi - Abdul Holik; Zulis Erwanto; Mohammad Aziz Yusuf (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Abstract. The Bulusan landfill of Banyuwangi has 1.5 ha to accommodate garbage from 13 districts with an input of 451.8 m3 of garbage per day and controlled landfill methods are carried out as garbage management. This research aims to evaluate the capacity of the Bulusan Landfill in Banyuwangi. Arithmetic, geometric and least square method were selected by the highest correlation value. The projection result of the Bulusan landfill for 2018 has been declared overloaded, with the height of embankment was higher than the planned embankment and it has not been able to accommodate garbage. The projection for the next 15 years from 2017 to 2031 was predicted that Bulusan landfill will be overloaded at 1.172.185 m3 of garbage volume. Financial and technical feasibility studies for candidates for the Bulusan landfill replacement need to be carried out so that the Bulusan landfill replacement project can be realized immediately.